Experimental investigation of metal- laminates with aerogel in high-temperature application - Mohammed, Ibrahim; Abu Talib, Abd Rahim (Aeronautical and Astronautical Society of the Republic of China , 台灣, 2021)
The study was based on the behavior of the fabricated composite that comprise of aluminium and a thin layer of epoxy/aerogel and coated with epoxy/different types of silica aerogel subjected to flame fire using a standard ISO2685 propane-air burner. The aim of this study is to fabricate a new, user friendly composite and to evaluate the behaviour of the composites in a pool fire by determining the penetration time of silica aerogels used. The composites were developed to resist a fire penetration based on the standard of temperature and heat flux for at least 15 minutes for fireproof and 5 minutes for fire resistance. The developed samples are one weight percent of aerogel in the mixture of resin/hardener and were mixed using mechanical mixer and sonicator. The results indicate that composite of GEATM 0.125 silica aerogel resists higher flame than the other types of aerogel composites examined, where it was 5.56% and 10.39% more fire resistance than Enova® IC3100 and Hamzel® respectively. The study reveals that the developed composites possess the required properties to be used.